2016
DOI: 10.1002/ppsc.201600197
|View full text |Cite
|
Sign up to set email alerts
|

Stable Fluorescence of Green‐Emitting Carbon Nanodots as a Potential Nanothermometer in Biological Media

Abstract: 1 of 7) 1600197Temperature measurement in biology and medical diagnostics is of great importance. Herein, a novel carbon nanodot (CND) based fluorescent nanothermometry device for spatially resolved temperature measurements is demonstrated. The fluorescence CNDs are prepared by a simple one-pot solvothermal method using sucrose as carbon source. Resultant CNDs show stable green fluorescence at 520 nm with high quantum yield (≈6%). The fluorescence of resultant CNDs exhibits a reversible linear response to temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…This phenomenon might be attributed to thermal agitation of nonradiative processes, the molecule collision frequency and the nonradiative transition rate increase at high temperature, reducing the intensity of the emission from the excited state. [46][47][48] The linear relationship between the uorescence intensity and temperature was within the range of 20-70 C. As revealed in Fig. 4b, the linear equation was F ¼ À23.96T + 3149.2 (R ¼ 0.94).…”
Section: Fluorescence Variation In Response To Temperaturementioning
confidence: 74%
“…This phenomenon might be attributed to thermal agitation of nonradiative processes, the molecule collision frequency and the nonradiative transition rate increase at high temperature, reducing the intensity of the emission from the excited state. [46][47][48] The linear relationship between the uorescence intensity and temperature was within the range of 20-70 C. As revealed in Fig. 4b, the linear equation was F ¼ À23.96T + 3149.2 (R ¼ 0.94).…”
Section: Fluorescence Variation In Response To Temperaturementioning
confidence: 74%
“…Recently, carbon dot optical probes have been investigated for temperature sensing applications in vivo and in vitro. 9,16,23,24,[35][36][37] Yang et al 24 reported the synthesis of low cytotoxic biocompatible carbon dots with temperaturedependent uorescence intensity from 20 to 80 C and a thermal sensitivity of 0.85% C À1 . They extended their work to show temperature-dependent uorescence in an in vivo mouse model.…”
Section: Introductionmentioning
confidence: 99%
“…This may explain the higher temperature sensitivity of the N-GQDs that are found in our works to have a high degree of functionalization [ 33 ]. Reversible temperature sensitivity been already observed with other carbon quantum dot based nanothermometers [ 17 , 35 , 37 , 44 ]. However, N-GQDs and RGQDs show a new variety of advantages including high biocompatibility evaluated previously via the thiazolyl blue tetrazolium bromide (MTT) and Luminescence assays, high visible quantum yields (N-GQDs) [ 33 ], simple and scalable synthesis, and potential for NIR temperature sensing (RGQDs) more applicable for in vivo studies [ 36 , 41 ].…”
Section: Resultsmentioning
confidence: 83%
“…It appears that the visible features of both N-GQDs and RGQDs experience monotonic decrease with temperature down to 19.3 and 16.8%, respectively, at 49 °C. Peak intensities quench linearly Recently, Kalytchuk et al suggested the mechanism behind this fluorescence intensity decrease due to a higher chance of obtaining non-radiative relaxation pathways from thermal effects [17,44]. Yang et al have also denoted that hydrogen bonds and oxygen-containing surface functional groups may play a role in the decrease of the fluorescence intensity with temperature enabling temperature-dependent excitation energy traps [33,37].…”
Section: Resultsmentioning
confidence: 99%